Evaluación de la resistencia de malezas a herbicidas en sistemas arroceros de secano - Vera Guerrero, Jose (2011)
This research work was carried out in the second half of 2011, on the grounds of the Farm "San Pablo" belonging to the Faculty of Agricultural Sciences at the Technical University of Babahoyo in the area of field and greenhouse, located in the 7.5 km road Babahoyo - Montalvo, with geographical coordinates 01 º 49 '15 "south latitude and 79032' west longitude and elevation of 8 m The area has a humid tropical climate, the average annual temperature of 25.60C., Precipitation of 2791.4mm., Relative humidity of 76% and 804.7 hours of heliophany. The soil is clay loam regular and flat topography, a trial was tested as herbicides; penoxsulam, pyribenzoxim, cyhalofop butyl ester, bispyribac sodium, profoxydim in weed resistance to herbicides. As genetic material was used planting certified seed of the rice variety "INIAP 14", obtained by the National Institute of Agricultural Research (INIAP), in order to evaluate the effects of herbicide application models, Bengal, Pyanchor, Clincher, Nominee100, Aura, applied at 15 days after sowing, to identify weed resistance to herbicides mentioned, also the economic analysis of grain yield based on the cost of treatments. The trial was conducted under the design "complete randomized blocks' with four replications and six treatment field and greenhouse work with the design entirely to chance. The doses of the herbicides were Penoxsulam - 1.0 l / ha, Profoxydim - 0.75 l / ha, bispyribac sodium - 0.5 l / ha, 1.0 Pyribenzoxim lt / ha (96.50%), butyl ester cyhalofop - 1.5 l / ha. and the control manual (weeding 20 to 40 and 60 days). Measured variables were subjected to analysis of variance, and used the statistical significance test of Duncan to 0.05% chance........